Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.11.17.516883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antagonistic role of the BTB-zinc finger transcription factors Chinmo and Broad-Complex in the juvenile/pupal transition and in growth control

Abstract: During development, the growing organism transits through a series of temporally regulated morphological stages to generate the adult form. In humans, for example, development progresses from childhood through to puberty and then to adulthood, when sexual maturity is attained. Similarly, in holometabolous insects, immature juveniles transit to the adult form through an intermediate pupal stage when larval tissues are eliminated and the imaginal progenitor cells form the adult structures. The identity of the la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The repression exerted by Br on early-larval enhancers and its role in terminating the juvenile developmental program, consequently inducing a permissive state for differentiation in wing cells, holds significance not only for developmental progression but also bears crucial implications for regeneration and tumor progression. Our findings, along with others (11, 22), strongly indicate that the regenerative capacity of damaged wing larval cells is contingent upon an environment lacking Br, thereby sustaining wing cells in a differentiation-refractory state. Indeed, it has been demonstrated that the wg 1 enhancer is activated in wing disc cells upon tissue injury, contributing to wing regeneration (25, 37), and further, this enhancer is repressed by Br in a context of tissue damage (38).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The repression exerted by Br on early-larval enhancers and its role in terminating the juvenile developmental program, consequently inducing a permissive state for differentiation in wing cells, holds significance not only for developmental progression but also bears crucial implications for regeneration and tumor progression. Our findings, along with others (11, 22), strongly indicate that the regenerative capacity of damaged wing larval cells is contingent upon an environment lacking Br, thereby sustaining wing cells in a differentiation-refractory state. Indeed, it has been demonstrated that the wg 1 enhancer is activated in wing disc cells upon tissue injury, contributing to wing regeneration (25, 37), and further, this enhancer is repressed by Br in a context of tissue damage (38).…”
Section: Discussionsupporting
confidence: 84%
“…Notably, this stage marks the transition of wing disc cells from a state refractory to differentiation to one permissive for differentiation. This transition is governed by the reciprocal repression between the larval specifier Chinmo and Br (10, 11, 22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have identified additional putative key components of this fate determination regulatory network (Truman & Riddiford, 2022;Chafino et al, 2023). Chronologically Inappropriate Morphogenesis (chinmo) gene, encoding a BTB/POZ transcription factor like Broad, was proposed instead to play the role of a larval master gene.…”
Section: (3) Fate Determination Genes Define Metamorphic Moultingmentioning
confidence: 99%